Efficacy of Organic Amendments, Biofumigants, and Mulches against Phytophthora nicotianae var. nicotianae Causing Leaf Blight and Fruit Rot Disease - Sharma, Shalini; Chandel, Sunita; Jandaik, Savita; Katoch, Vijeta (International Journal of Bio-resource and Stress Management, 2025)
An experiment was conducted during the 2022 and 2023 growing seasons, from April to August, at the experimental farm of the Department of Plant Pathology, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India. The study aimed to explore the efficacy of various organic amendments, biofumigant crops, and mulches in mitigating losses caused by leaf blight and fruit rot, a significant disease affecting bell pepper production. The disease is prevalent all over the world wherever warm-humid conditions exist during the growing season. Different organic amendments viz; neem cake, cotton cake, mustard cake, vermicompost, sawdust, dried residues of cabbage, cauliflower, mustard and radish @500 g m-2; pine needles, wheat straw and polyethylene mulches were tested in field against the leaf blight and fruit rot disease. The trial was conducted in a completely randomized block design (RBD) keeping three replications in each treatment. Among the various treatments used, black polyethylene mulch, pine needle mulch, dried crop residue powder and oil cakes of mustard, when applied 10 days prior to planting of bell pepper seedlings in field resulted in maximum reduction of fruit rot incidence and leaf blight severity and also significantly increased the fruit yield. Thus, incorporating these treatments for the management of disease offers a promising, sustainable approach for improving the health and productivity of bell pepper, while also supporting sustainable agricultural practices by reducing reliance on chemical treatments.